Ypt4 and lvs1 regulate vacuolar size and function in Schizosaccharomyces pombe. Issue 3 (3rd July 2017) - Rains, Addison; Bryant, Yorisha; Dorsett, Kaitlyn A.; Culver, Austin; Egbaria, Jamal; Williams, Austin; Barnes, Matt; Lamere, Raeann; Rossi, Austin R.; Waldrep, Stephanie C.; Wilder, Caroline; Kliossis, Elliot; et al.
ABSTRACT: The yeast vacuole plays key roles in cellular stress responses. Here, we show that deletion of lvs1, the fission yeast homolog of the Chediak-Higashi Syndrome CHS1 / LYST gene, increases vacuolar size, similar to deletion of the Rab4 homolog ypt4 . Overexpression of lvs1-YFP rescued vacuolar size in ypt4Δ cells, but ypt4-YFP did not rescue lvs1Δ, suggesting that lvs1 may act downstream of ypt4 . Vacuoles were capable of hypotonic shock-induced fusion and recovery in both ypt4Δ and lvs1Δ cells, although recovery may be slightly delayed in ypt4Δ . Endocytic and secretory trafficking were not affected, but ypt4Δ and lvs1Δ strains were sensitive to neutral pH and CaCl2, consistent with vacuolar dysfunction. In addition to changes in vacuolar size, deletion of ypt4 also dramatically increased cell size, similar to tor1 mutants. These results implicate ypt4 and lvs1 in maintenance of vacuolar size and suggest that ypt4 may link vacuolar homeostasis to cell cycle progression.